Penerapan Prinsip-Prinsip Animasi Pada Film Pendek Animasi “Nohoax” - Gerson Julyfer Parulian Tambun; Wahyu Adhitya; Ilmi Nazar Hamdi; Selly Artaty Zega (Politeknik Negeri Batam, 2022)
Animation is one of the media that is often used to convey information, communication media, and entertainment. Animation is a collection of images arranged in an orderly manner following the flow of movement at a certain timeline to create the illusion of moving images. The image can be any object such as a character, object, or text. Animation is no longer foreign to us, especially children, this is because we often enjoy animated content, whether in cinemas, YouTube videos, or TV shows. An animated short film entitled “nohoax” is one of the implementations. “nohoax” animation tells about two young people who want to stop hoax news circulating in the community by creating a hoax news detection application. The purpose of this study is to explain and describe the application of animation principles in the animated short film “nohoax”. This study uses descriptive qualitative research methods by observing “nohoax” animation, conducting interviews with parties who understand and have knowledge of the principles of animation, and using literature that discusses the principles of animation. The results of this study describe the principles of animation used in “nohoax” animated short films and show the application of animation principles to “nohoax” animated short films to make animations look more alive and interesting.